2015
DOI: 10.1097/psy.0000000000000151
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Mental Disorders and Physical Diseases in Adolescents From a Nationally Representative Cohort

Abstract: Findings suggest that mental disorders and physical diseases often co-occur in childhood. This association is a major public health challenge, and the child health system needs additional strategies in patient-centered care, research, medical education, health policy, and economics to develop well-coordinated interdisciplinary approaches linking mental and physical care in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 69 publications
4
33
0
1
Order By: Relevance
“…3638 Further research is needed, particularly longitudinal studies that examine the antecedents and health sequelae of mental health, substance dependence, and psychiatric comorbidities across adolescent and young adult development to identify optimal timing and targets for psychosocial interventions in relation to gender affirmation and gender role transitions. 39,40 …”
Section: Discussionmentioning
confidence: 99%
“…3638 Further research is needed, particularly longitudinal studies that examine the antecedents and health sequelae of mental health, substance dependence, and psychiatric comorbidities across adolescent and young adult development to identify optimal timing and targets for psychosocial interventions in relation to gender affirmation and gender role transitions. 39,40 …”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of medical conditions in a mental population estimated varied considerably due to different measurement and study populations . In past research, most mental disorders were identified using epidemiological self‐report during a structured or semistructured interview . Clinical trials have examined only specific populations and settings, and systematic reviews and meta‐analyses may be influenced by publication bias .…”
Section: Introductionmentioning
confidence: 99%
“…Based on the above, numerous studies have examined psychological and psychiatric comorbidities in adolescents or elderly; however, few studies have comprehensively explored the association between all and individual mental disorders and medical comorbidities . Besides, most of the past studies only separately investigated the risk of medical conditions in people with a mental health condition, and few of them manage associations among two and more comorbidities simultaneously .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found higher rates of comorbid medical conditions among adolescents with BHCs; a recent national survey found that more than one-third of respondents reported at least 1 mental disorder and 1 physical disorder. 11 Asthma, diabetes, heart disease, infectious diseases, and digestive disorders have all been found to be associated with an increased prevalence of BHCs at some point in their lives. 11,24 Comorbidity between BHCs and medical conditions can also complicate treatment regimens, 25 increase health care use and costs, 26 and compromise health outcomes, 9,27 which supports the need for a better understanding of the prevalence of these comorbidities.…”
Section: Journal Of the American Academy Of Child And Adolescent Psychimentioning
confidence: 99%
“…[4][5][6][7][8] The pediatric literature on the co-occurrence of mental health, substance use, and medical conditions is less robust, but has begun to document comorbidity between BHCs and some common chronic medical conditions. [9][10][11] A recent national population survey found that among 18-year-olds, 31.9% reported having an anxiety disorder, 14.3% a mood disorder, 19.6% a behavioral disorder, including attention-deficit/hyperactivity disorder (ADHD), and 11.4% a SUD at some point in their lives. 12 High rates of mental health and SUD comorbidity have also been documented, particularly in clinical samples.…”
mentioning
confidence: 99%